HP48 : Coexistence of unilateral and bilateral retinitis pigmentosa in the same family. (March 2022) - Melgar Jiménez, B.; Zabalo San Juan, J.; Echeverría Guibert, T.; Cascón Fuertes, G.; Sánchez Aparicio, J.A.; Gener, B.; Fernández Bedoya, A.I.; Yurrebaso Santamaría, I.
Abstract : To study a patient with unilateral retinitis pigmentosa who has a child with bilateral affection. CASE REPORT : A 40 year-old woman presented decreased peripheral visual acuity (VA) of the left eye at the age of 37. Best-corrected VA for her left eye was 0.4. Dilated fundus examination showed diffuse peripheral retinal atrophy and bone spicule pigmentary changes. Optical Coherence Tomography (OCT) revealed retinal atrophy and disruption of external layers in the extrafoveal area. Examination of the right eye was completely normal. However, her 8 year-old asymptomatic daughter, shows bilateral retinitis pigmentosa (RP). VISUAL EVOKED POTENTIALS (VEP)–ELECTRORETINOGRAM (ERG): Neurophysiological study was performed one year after clinical onset. VEP-pattern was normal. ERG-flash presented absent responses on scotopic and photopic examinations of the left eye. Right eye examination was normal. This study was compatible with a unilateral RP with a preserved central region. Exome sequencing did not identify pathogenic or likely pathogenic variants in 136 genes associated with RP. Genetic testing in the daughter is ongoing. EVOLUTION: The patient has progressively worsened both clinically and in successive neurophysiological studies. Best-corrected VA is now <0.05 (Counting Fingers) in her left eye and the Goggle-VEP is pathologic. For the asymptomatic right eye all examinations remain normal. CONCLUSION: Unilateral RP is a rare condition of unknown aetiology in most cases. To our knowledge, this is the first case reported of occurrence of unilateral and bilateral RP in the same family. Ophthalmological and neurophysiological examinations of family members of patients with unilateral RP are highly recommended.